2023
DOI: 10.1136/annrheumdis-2020-219787
|View full text |Cite
|
Sign up to set email alerts
|

Response to: ‘Correspondence on ‘Association between treatment with colchicine and improved survival in a single-centre cohort of adult hospitalised patients with COVID-19 pneumonia and acute respiratory distress syndrome’’ by Kawada

Abstract: Correspondence responsePatient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research. Patient consent for publication Not required. Ethics approvalThe off-label use of colchicine was supported by the hospital administration as the emergency situation of COVID-19, which was particularly severe in Lombardy with dozens of new patients on a daily basis, had to be managed quickly and amid shortage of 'Standard of Care' tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…For all of these trials, the most common adverse event was diarrhea, especially among patients treated with colchicine, while no safety concerns with regard to infections were recorded. Several other observational studies reported encouraging results, with few, tolerable side effects [24,25,[27][28][29][89][90][91][92] (Table 2). Piantoni et al also reported about long-term results, describing an improved survival in patients treated with colchicine compared with standard-of-care (mortality rate at 270 days: 20% vs. 44%, p = 0.0001) [91].…”
Section: Colchicine To Treat Covid-19: What Is the Rationale?mentioning
confidence: 96%
“…For all of these trials, the most common adverse event was diarrhea, especially among patients treated with colchicine, while no safety concerns with regard to infections were recorded. Several other observational studies reported encouraging results, with few, tolerable side effects [24,25,[27][28][29][89][90][91][92] (Table 2). Piantoni et al also reported about long-term results, describing an improved survival in patients treated with colchicine compared with standard-of-care (mortality rate at 270 days: 20% vs. 44%, p = 0.0001) [91].…”
Section: Colchicine To Treat Covid-19: What Is the Rationale?mentioning
confidence: 96%
“…A meta-analysis demonstrated the efficacy of colchicine in COVID-19 management [ 128 ]. Accordingly, a better survival rate of patients with severe COVID-19 on colchicine therapy at the day of 8 compared to standard therapy has been reported, which is attributed to inhibition of central pro-inflammatory cytokines responsible for ARDS [ 129 ]. Furthermore, colchicine administration in COVID-19 patients on the fifth day of fever or after the 8th day of influenza-like symptoms initiation was recommended by Della-Torre et al.…”
Section: Purinergic System Inhibitors Encouraging Agents For Attenuating the Cytokine Stormmentioning
confidence: 99%
“…3 We have recently reevaluated, 6 months after Hospital discharge, 99 patients out of a series of 272 consecutively admitted to Esine Hospital for COVID19 pneumonia between March 5th and April 5th, 2020. 4 Considering patients who died in the meanwhile, 5 these represent the 54% of all the evaluable cohort. Notably, 6 months after discharge, 53% of these patients reported persistent dyspnea or cough.…”
mentioning
confidence: 99%
“…Patients 1 and 2 were included in our original descriptions of Esine cohorts. 4,5 The first patient is a 48-year-old healthy man, admitted (16th March) for dyspnea, cough and fever, who developed SARS-CoV-2-pneumonia. He was treated with antivirals (darunavir/ ritonavir), hydroxychloroquine, high-flow oxygen in continuous positive airway pressure (C-PAP) mode.…”
mentioning
confidence: 99%
See 1 more Smart Citation